A large interhemispheric glioependymal cyst associated with partial defect of the corpus callosum in an elderly man. Issue 5 (14th July 2020) - Takayama, Mio; Kashiwagi, Masayuki; Hara, Kenji; Matsusue, Aya; Waters, Brian; Kubo, Shin‐ichi
Abstract : Interhemispheric cysts are congenital, and usually present symptoms during childhood. However, they are occasionally detected in adults. These cystic lesions are sometimes associated with defects of the corpus callosum. Although defects of the corpus callosum by themselves do not present clinical symptoms, they are often accompanied by other brain malformations. A man in his late 60s was found dead at the scene of a fire. At autopsy, his brain weighed 1223 g and had a large interhemispheric cyst, measuring 5.5 × 4.5 × 4.0 cm in size. The cyst contained clear fluid but was not connected to the ventricular system. On slices of the cerebrum, the corpus callosum did not connect the right and left cerebral hemispheres, and the right lateral ventricle was dilated. By the existence of the cyst, compressed by the cyst, the hemispheres were displaced on either side. Histologically, the cerebral parenchyma around the cyst was slightly edematous but structurally normal. Immunohistochemically, both glial fibrillary acidic protein and podoplanin were expressed in the cystic components. Thus, the cystic lesion was diagnosed as a glioependymal cyst. In this case, because the cyst was located at the interhemispheric space between the right and left frontal lobes, the individual experienced no obvious symptoms, despite its large size. The individual's brain malformations included the partial defect of the corpus callosum and the cyst. The dilation of the right lateral ventricle was considered to result from the location of the cyst. Under the influence of the cyst, the third ventricle was displaced downward, and one or both of the interventricular foramen were obstructed. The decedent had burns over his whole body. Burns to the epiglottis and soot in the airway were also observed. Volatile hydrocarbons, such as benzene and styrene, were detected in the blood. The percentage of carboxyhemoglobin levels in a total of hemoglobin levels were 19‐25%. Therefore, the individual's cause of death was established as death by fire.